Decadal Attribution of Historic Temperature and Ocean Heat Content Change to Anthropogenic Emissions. Issue 3 (7th February 2020) - Larson, E. J. L.; Portmann, R. W.; Solomon, S.; Murphy, D. M.
Abstract: We present an alternative method of calculating the historical effective radiative forcing using the observed temperature record and a kernel based on the 5th Climate Model Intercomparison Project (CMIP5) temperature response. This estimate is the effective radiative forcing time series that the average climate model would need to simulate the observed global mean surface temperature anomalies. We further infer the anthropogenic aerosols radiative forcing as a residual using the better‐known greenhouse gas radiative forcing. This allows an independent estimate of anthropogenic aerosol radiative forcing, which suggests a cooling influence due to aerosols in the early part of the twentieth century. The temporal kernels are also used to calculate decadal contributions from the dominant forcing agents to present‐day temperature, ocean heat content, and thermosteric sea level rise. The current global mean temperature anomaly is dominated by emissions in the past two decades, while current ocean heat content is more strongly affected by earlier decades. Key Points: We calculate effective radiative forcing by applying model‐derived kernels to observational estimates of global mean surface temperature Our independent estimate of anthropogenic aerosol forcing suggests substantial cooling due to aerosols in the early part of the twentieth century We attribute current temperature change and sea level rise to past decadal emissions using temporal kernels